Confocal sputtering of (111) orientated smooth gold films for surface plasmon resonance approaches. (April 2017) - Schmidl, G.; Dellith, J.; Teller, N.; Bochmann, A.; Teichert, S.; Stranik, O.; Dathe, A.; Tympel, V.; Schmidl, F.; Kessler, E.; Wieduwilt, T.; Fritzsche, W.
Abstract: We report on the influence of sputtering parameters on the microstructural growth of 200 nm thick Au layers and, moreover, on their crystalline, electrical, and optical properties using a confocal sputtering arrangement. The confocal sputtering arrangement allows the production of highly homogeneous layer thicknesses that depend on pressure, power, and target-substrate distance. Layers deposited at low Ar pressure show extremely smooth and densely-packed films, as well as a preferred {111}-texture contrary to films deposited at higher Ar pressure. Furthermore, an increase in electrical resistivity combined with a decrease in grain size is observed for these layers. A subsequent annealing process up to a temperature of 600 °C reduces the resistivity, increases the grain size, improves the fraction of {111}-texture, and significantly changes the surface morphology for all initial states. Investigations at 4.2 K showed that the decrease in resistivity is caused by a structural change that takes the number of grain boundaries into consideration. The dielectric function investigated by ellipsometric measurements is dependent on the deposition process parameters, especially on Ar pressure. Surface plasmon resonance calculations based on the layers produced using the Otto configuration show the best performance using a specific setup for layers deposited at low Ar pressure. Highlights: Low pressure sputtering exhibits smooth densely-packed gold layers with a preferred (111) orientated fiber texture. A high quality factor of surface plasmon propagation is achieved for the shown low pressure deposition. The (111) orientation can be improved for all initial states by a post deposition annealing process. In general, the annealing process influences positively structural, morphological and electrical layer properties. In case of high pressure deposition an annealing process is counterproductive to improve the optical constants.